Inovasi Public Relations dalam Meningkatkan Hubungan Pelanggan di Sektor Keuangan Digital - kamilah, nila farchatul (Maliki Interdisciplinary Journal, 2025)
Innovation in public relations is key to strengthening customer relationships in the era of digital finance, especially for Islamic banks. Amidst fierce competition and rapid technological development, Islamic banks are faced with the challenge of meeting higher customer expectations. This research explores how a deep understanding of customer needs can trigger a more responsive and personalized service transformation. By leveraging digital technology, banks can not only improve efficiency, but also create a more satisfying customer experience, leading to stronger loyalty. In addition, strategic collaboration with fintech companies offers innovative opportunities to deliver more relevant and engaging financial solutions. These findings suggest that success in digital banking depends not only on technology, but also on banks’ ability to build close and mutually beneficial relationships with customers. As such, innovation in public relations and digital services is an important foundation for gaining competitive advantage in the future.